2022
DOI: 10.17977/um024v7i12022p039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fibre Volume Fraction and Sodium Hydroxide Treatment on Mechanical Properties of Palm Fibre/Unsaturated Polyester Composite

Abstract: Wood has some weaknesses, such as susceptibility to weathering, easily attacked by termites, and low water resistance. An alternative material such as Natural Fibre-Reinforced Polymer (NFRP) composite should overcome those weaknesses. This research aims to make a composite with palm fibre and unsaturated polyester resin. Palm fibres immerse for 2 hours in NaOH solution with varying concentrations of 3%, 5%, and 7%. The volume fraction of palm fibre are 0%, 5%, 10%, 15%, and 20%. Woven roving fibreglass was add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This study showed that treatment with 0.125% potassium permanganate resulted in stronger tensile strength than alkalization treatment with 6% sodium hydroxide. The highest tensile strength is 9 MPa, whereas with sodium hydroxide alkalization treatment it is less than 6 MPa [16].…”
Section: Introductionmentioning
confidence: 93%
“…This study showed that treatment with 0.125% potassium permanganate resulted in stronger tensile strength than alkalization treatment with 6% sodium hydroxide. The highest tensile strength is 9 MPa, whereas with sodium hydroxide alkalization treatment it is less than 6 MPa [16].…”
Section: Introductionmentioning
confidence: 93%